Development of novel quality control material based on CRISPR/Cas9 editing and xenografts for MLH1 protein deficiency testing. Issue 5 (7th April 2021) - Li, Rui; Zhang, Runling; Tan, Ping; Wang, Meng; Chen, Yuqing; Zhang, Jiawei; Han, Dongsheng; Han, Yanxi; Li, Jinming; Zhang, Rui
Abstract: Background: Mismatch repair deficiency (dMMR) status induced by MLH1 protein deficiency plays a pivotal role in therapeutic decision‐making for cancer patients. Appropriate quality control (QC) materials are necessary for monitoring the accuracy of MLH1 protein deficiency assays used in clinical laboratories. Methods: CRISPR/Cas9 technology was used to edit the MLH1 gene of GM12878Cas9 cells to establish MLH1 protein‐deficient cell lines. The positive cell lines were screened and validated by Sanger sequencing, Western blot (WB), and next‐generation sequencing (NGS) and were then used to prepare formalin‐fixed, paraffin‐embedded (FFPE) samples through xenografting. These FFPE samples were tested by hematoxylin and eosin (H&E) staining and immunohistochemistry (IHC) for suitability as novel QC materials for MLH1 protein deficiency testing. Results: We successfully cultured 358 monoclonal cells, with a survival rate of 37.3% (358/960) of the sorted monoclonal cells. Through Sanger sequencing, cell lines with MLH1 gene mutation were identified. Subsequently, two cell lines with MLH1 protein deficiency were identified by WB and named as GM12878Cas9_6 and GM12878Cas9_10. The NGS results further confirmed that the MLH1 gene mutation in these two cell lines would cause the formation of stop codons and terminate the expression of the MLH1 protein. The H&E staining and IHC results also verified the deficiency of the MLH1 protein, and FFPE samples from xenografts proved their similarity and consistency with clinical samples. Conclusions: We successfully established MLH1 protein‐deficient cell lines. Followed by xenografting, we developed novel FFPE QC materials with homogenous, sustainable, and typical histological structures advantages that are suitable for the standardization of clinical IHC methods. Abstract : CRISPR/Cas9 technology was used to edit the MLH1 gene of GM12878Cas9 cells to establish MLH1 protein‐deficient cell lines. Cell lines with MLH1 gene mutation and MLH1 protein deficiency were identified by Sanger sequencing and Western blot (WB). Followed by xenografting, we developed novel formalin‐fixed, paraffin‐embedded (FFPE) samples quality control (QC) materials with homogenous, sustainable, and typical histological structure advantages that are suitable for the standardization of clinical immunohistochemistry (IHC) methods.